Metastases in patients with malignant melanoma despite of negative sentinel lymph node: Has the concept to be changed? - Weiss, M.; Konz, B.; Schmid-Wendtner, M. H.; Sander, C.; Dresel, S.; Tatsch, K.; Volkenandt, M.; Hahn, K. (Nuklearmedizin - NuclearMedicine, 2000)
Aim: The Sentinel Lymph Node (SLN) is of considerable prognostic relevance, because extended lymph node dissection may not be performed in patients presenting with histologically negative SLN. The aim of the present study was to prove the prognostic value of the SLN-concept in these patients. Methods: So far the clinical follow-up of 162 patients with histologically proven malignant melanoma and metastatically uninvolved (negative) SLN was investigated. Histological examination included standard methods (HE-Test) and special histochemical techniques (S-100, HMB-45). All patients underwent clinical examination, ultrasonic diagnosis of the regional lymph nodes, and x-ray of the chest every 3 months. Results: Despite of negative SLN-findings in 8/162 patients metastases of the malignant melanoma were found after a time period of 5-27 months. Three patients presented with recurrence in the previously mapped (negative) SLN-basin. In another case the scintigraphically visualized SLN could not be identified intraoperativelly by means of the hand-held gamma probe. One patient showed intransit-metastases or skin-metastases, respectively; another patient recurred in the scar area. One patient showed hematogenic dissemination (liver) which is not detectable by lymphoscintigraphy; in another patient metastases were found outside the primary lymphatic basin (cervical). Conclusion: In our patient group 4,9% presented with metastases despite negative SLN while published data report up to 11% (observation period 35 months), among them only 3 patients (1,9%) being real concept failures. Our results underline that there is no evidence to change this concept in patients with clinically early stage.
Keywords: Sentinel Lymph Node; malignant melanoma; lymph scintigraphy